A New Determinant of Candida glabrata Virulence: The Acetate Exporter CgDtr1 - Romão, Daniela; Cavalheiro, Mafalda; Mil-Homens, Dalila; Santos, Rui; Pais, Pedro; Costa, Catarina; Takahashi-Nakaguchi, Azusa; Fialho, Arsénio M.; Chibana, Hiroji; Teixeira, Miguel C. (Frontiers in Cellular and Infection Microbiology, 2017)
Persistence and virulence of Candida glabrata infections are multifactorial phenomena, whose understanding is crucial to design more suitable therapeutic strategies. In this study, the putative multidrug transporter CgDtr1, encoded by ORF CAGL0M06281g, is identified as a determinant of C. glabrata virulence in the infection model Galleria mellonella. CgDTR1 deletion is shown to decrease the ability to kill G. mellonella larvae by decreasing C. glabrata ability to proliferate in G. mellonella hemolymph, and to tolerate the action of hemocytes. The possible role of CgDtr1 in the resistance to several stress factors that underlie death induced by phagocytosis was assessed. CgDTR1 was found to confer resistance to oxidative and acetic acid stress. Consistently, CgDtr1 was found to be a plasma membrane acetic acid exporter, relieving the stress induced upon C. glabrata cells within hemocytes, and thus enabling increased proliferation and virulence against G. mellonella larvae.